2010
DOI: 10.1248/bpb.33.1400
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Ezrin and CLP36 in the Two Layers of Syncytiotrophoblast in Rats

Abstract: The syncytiotrophoblast in the placenta serves as an interface for efficient maternal-fetal exchange of nutrients, metabolites and xenobiotic compounds, and membrane transport processes play pivotal roles in efficient uptake of certain compounds and in exclusion of others; this is referred to as the blood-placenta barrier. 1,2) In humans, the syncytiotrophoblast is derived from cell fusion of the progenitor cytotrophoblast and consists a polar single epithelium. The apical and basal plasma membranes of the syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…Ezrin was primarily expressed in the labyrinth zone of placenta (Figure 1B), and was predominantly localized at the apical membrane of syncytiotrophoblast in placenta of Ez +/+ fetal mice (Figure 1B), in accordance with previous observations in rat placenta [14]. Intrauterine growth retardation was observed at gestational day 15.5 and later in Ez −/− mice (Figure 3).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Ezrin was primarily expressed in the labyrinth zone of placenta (Figure 1B), and was predominantly localized at the apical membrane of syncytiotrophoblast in placenta of Ez +/+ fetal mice (Figure 1B), in accordance with previous observations in rat placenta [14]. Intrauterine growth retardation was observed at gestational day 15.5 and later in Ez −/− mice (Figure 3).…”
Section: Discussionsupporting
confidence: 89%
“…Recent studies indicate that the functional expression of some apical membrane transporters such as cystic fibrosis transmembrane conductance regulator (CFTR) and Na + /H + exchanger (NHE3) is regulated by their interaction with ezrin in the kidney and respiratory tract [9][11]. Ezrin is the most abundant of the ERM proteins and is specifically associated with the apical membrane of syncytiotrophoblast [12][14]. Thus, transporter/ezrin complexes are considered to be important for the proper transport of physiological nutrients and metabolites in syncytiotrophoblast.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a lack of data on in vitro cell lines derived from human gestational trophoblastic tumors, several histopathological studies have demonstrated the strong expression of PD-L1 in the plasma membrane of tumor cells obtained from human gestational trophoblastic neoplasia [ 10 , 12 , 13 ]. In addition, Higuchi et al immunohistochemically identified that ezrin is highly localized in the apical membranes of a syncytiotrophoblast cell line, which is a source of GTN derived from rat placenta [ 43 ]. Taken together, these findings suggest that PD-L1, ezrin, and radixin, but not moesin, are highly expressed at the genetic and protein levels in JEG-3 cells, and that PD-L1 is co-localized with ezrin and radixin in the plasma membrane of this cell line.…”
Section: Discussionmentioning
confidence: 99%
“…The TR‐TBTs were established by Kitano et al14 The cells exhibited typical characteristics of in vivo syncytiotrophoblast 14. Especially, they were testified to form a polarized layer of cells, with the apical and basolateral membranes having functional similarities to those in rat placenta 14,17. In addition, TR‐TBTs express many transporter genes found in the human placenta and also exhibit the uptake activity of taurine and gamma‐aminobutyric acid through several transporters 6.…”
Section: Discussionmentioning
confidence: 99%
“…5). It is known that the syncytiotrophoblast of rat is composed of two layers, SynI (maternal‐side) and SynII (fetal‐side) 17. TR‐TBT 18d‐1 and TR‐TBT 18d‐2 are derived from SynI and SynII in rat, respectively 14.…”
Section: Discussionmentioning
confidence: 99%